Immersion Phased Array Ultrasonic Inspection for Aluminum Liner of Carbon Fibre Composite Overwrapped Pressure Vessel - Tao, Yangji; Liu, Zhongqiang; Tang, Ping; Miao, Cunjian; Teng, Guoyang; Shi, Yan (Transactions on Environment, Energy and Earth Sciences, 2024)
Carbon fibre composite overwrapped pressure vessels (type pressure vessels for short) are widely used in hydrogen fuel cell vehicles. The aluminum liner of type pressure vessels bearing the hydrogen pressure and fiber tension simultaneously requires factory inspections. It is difficult to detect the aluminum liner with different curvature by the phased array ultrasonic testing. An aluminum liner detection method was proposed based on the immersion phased array ultrasonic testing. The thickness of the aluminum liner was measured by avoiding overlapping reflected waves. Besides, the longitudinal defects were detected by the circumferential shear wave scanning, and transverse defects were detected by the bidirectional deflecting scanning. The above three modes were verified by the acoustic field simulation and inspection simulation using CIVA. Results show that the proposed detection method is highly reliable for the thickness measurement and defect detection of the aluminum liner.